2016
DOI: 10.1111/zph.12249
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge and Attitudes Regarding the Use of Antibiotics and Resistance: Findings from a Cross‐Sectional Study Among Palestinian Adults

Abstract: Antibiotics are considered to be among the most commonly sold drug classes in Palestine. Resistance to antibiotics has increased for reasons relating to the use and misuse of antibiotics. The aim of this study was to evaluate the knowledge, and attitudes regarding antibiotic use and awareness about resistance among adults visiting the emergency departments at hospitals in North Palestine. A self-administered cross-sectional questionnaire survey involving participants aged 18 or over was conducted from June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
20
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
10
20
1
2
Order By: Relevance
“…The only sociodemographic factor found to be associated with each of knowledge, attitudes and practices relating to antibiotics use was education. Respondents with higher education had better knowledge and more appropriate attitudes and practices, a finding consistent with other studies [5, 7, 13, 55, 5760]. Our findings also suggest respondents in urban areas had better knowledge on antibiotic use than those in rural areas, a similar observation to that found in a Lithuanian study [61] but contrasting with a Polish study that found no such difference [62].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The only sociodemographic factor found to be associated with each of knowledge, attitudes and practices relating to antibiotics use was education. Respondents with higher education had better knowledge and more appropriate attitudes and practices, a finding consistent with other studies [5, 7, 13, 55, 5760]. Our findings also suggest respondents in urban areas had better knowledge on antibiotic use than those in rural areas, a similar observation to that found in a Lithuanian study [61] but contrasting with a Polish study that found no such difference [62].…”
Section: Discussionsupporting
confidence: 90%
“…Although respondents were aware that antibiotic resistance was a problem, half (50.9%) were still unsure whether “ skipping one or two doses does not contribute to the development of antibiotic resistance ”. This finding is consistent with a Palestinian study that found one-third of respondents knew the meaning of antibiotic resistance, however nearly one-third of them incorrectly agreed that antibiotics’ effectiveness would not be affected if antibiotics are taken less or more than the prescribed dose [57].…”
Section: Discussionsupporting
confidence: 86%
“…11 impressively, 94% of respondents from Sweden, Tanzania, the United arab emirates, and Palestine appeared to have a good knowledge of aBR and even the resistance development (⩾90%) noting that, the more antibiotics are used in the society, the higher the risk of developing and spreading resistance. 21,22 Participants, according to Hawking et al, 30 however, displayed their basic knowledge, after being prompted, to help create awareness. while some respondents disagreed that aBR was a serious problem in our society, whether locally or globally, 18 students who demonstrated more knowledge of the subject insisted on the fact that the current level of awareness was highly inadequate.…”
Section: Self-medication and Use Of Leftover Antibioticsmentioning
confidence: 99%
“…Patient referral to drug treatment centres was a challenge (Foley et al, 2018;Parry et al, 2017). On the other hand, consumers with low level of education (Farha et al, 2016;Haddad & Ebada, 2017;Yong-Kang, 2018), lack of appropriate knowledge about medication use (Abu Taha et al, 2016;Tara Carney et al, 2016;Jaber et al, 2015;Peng et al, 2018;X. Wang et al, 2017;Yaylaci et al, 2017), lack of awareness regarding potential risks (Tara Carney et al, 2016;Farha et al, 2016;Jaber et al, 2015;Yong-Kang, 2018), poor attitude toward medication usage (Abu Taha et al, 2016;Gu et al, 2015;Jaber et al, 2015) were disproportionally burdened by diversion and misuse.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, consumers with low level of education (Farha et al, 2016;Haddad & Ebada, 2017;Yong-Kang, 2018), lack of appropriate knowledge about medication use (Abu Taha et al, 2016;Tara Carney et al, 2016;Jaber et al, 2015;Peng et al, 2018;X. Wang et al, 2017;Yaylaci et al, 2017), lack of awareness regarding potential risks (Tara Carney et al, 2016;Farha et al, 2016;Jaber et al, 2015;Yong-Kang, 2018), poor attitude toward medication usage (Abu Taha et al, 2016;Gu et al, 2015;Jaber et al, 2015) were disproportionally burdened by diversion and misuse. Meanwhile consumers with early life experiences (Van Hout, Norman, et al, 2017), mental health problems (Guo et al, 2017), recreational use purpose (Foley et al, 2018;Wells et al, 2018) and biopsychosocial purposes of use were more affected.…”
Section: Discussionmentioning
confidence: 99%